Genomic Variations in SARS-CoV-2 Genomes From Gujarat: Underlying Role of Variants in Disease Epidemiology - Joshi, Madhvi; Puvar, Apurvasinh; Kumar, Dinesh; Ansari, Afzal; Pandya, Maharshi; Raval, Janvi; Patel, Zarna; Trivedi, Pinal; Gandhi, Monika; Pandya, Labdhi; Patel, Komal; Savaliya, Nitin; et al. (Frontiers in Genetics, 2021)
Humanity has seen numerous pandemics during its course of evolution. The list includes several incidents from the past such as Measles, Ebola, SARS, MERS, etc. The latest edition to this is COVID-19, caused by the novel coronavirus, SARS-CoV-2. As of 18th August 2020, COVID-19 has affected over 21 million people from 180+ countries, and 0.7 million deaths across the globe. Genomic technologies have enabled us to understand the genomic constitution of the pathogens, their virulence, evolution, rate of mutations, etc. To date, more than 83,000 viral genomes have been deposited in public repositories like GISAID and NCBI. While we are writing this, India is the 3rd most-affected country by COVID-19 with 2.7 million cases, and >53,000 deaths. Gujarat is the eleventh highest affected state with a 3.48% death rate compared to the national average of 1.91%. In this study, a total of 502 SARS-CoV-2 genomes from Gujarat have been sequenced and analyzed to understand its phylogenetic distribution and variants against global and national sequences. Further variants were analysed from diseased and recovered patients from Gujarat and World to understand its role in pathogenesis. Among the missense mutations, present in Gujarat SARS-CoV-2 genomes, C28854T (Ser194Leu) with allele frequency of 47.62% and 7.25% in deceased patients from Gujarat and global dataset respectively. In contrast, the allele frequency of 35.16% and 3.20% was observed in recovered patients from Gujarat and Global dataset respectively. It is a deleterious mutation present in nucleocapsid (N) gene and is significantly associated with mortality in Gujarat patients with a p-value of 0.067 and in global dataset with p-value of 0.000924. The other deleterious variant identified in deceased patients from Gujarat (p-value of 0.355) and the world (p-value of 2.43E-06) is G25563T, which is located in Orf3a and has a potential role in viral pathogenesis. SARS-CoV-2 genomes from Gujarat are forming distinct clusters under the GH clade of GISAID. This study shed light on viral haplotype in SARS-CoV-2 samples from Gujarat, India.